Risk of Parenteral Nutrition in Neonates—An Overview - Zingg, Walter (MDPI, 2012)
Healthcare-associated infections (HAI) in preterm infants are a challenge to the care of these fragile patients. HAI-incidence rates range from 6 to 27 infections per 1000 patient-days. Most nosocomial infections are bloodstream infections and of these, the majority is associated with the use of central venous catheters. Many studies identified parenteral nutrition as an independent risk factor for HAI, catheter-associated bloodstream infection, and clinical sepsis. This fact and various published outbreaks due to contaminated parenteral nutrition preparations highlight the importance of appropriate standards in the preparation and handling of intravenous solutions and parenteral nutrition. Ready-to-use parenteral nutrition formulations may provide additional safety in this context. However, there is concern that such formulations may result in overfeeding and necrotizing enterocolitis. Given the risk for catheter-associated infection, handling with parenteral nutrition should be minimized and the duration shortened. Further research is required about this topic.